The Impact of Social Capital and Collaboration Quality of E-Government Systems on Knowledge Sharing Behavior in Saudi Arabia - Alsindi, Saleh (Curtin University, 2021)
The research investigates the impact of social capital and collaboration quality on knowledge sharing behaviour in e-government systems in Saudi Arabia. It employed sequential explanatory mixed methods in which a quantitative phase was followed by a qualitative phase. The first phase tested the research model, and the second phase explained and elaborated the findings of the first. The findings provide a deeper understanding of social capital theory, and practical recommendations are provided which may be helpful to public sector organisations.